Cognitive decline : strategies for prevention - Fillit, Howard; Butler, Robert N., 1927-2010 (Greenwich Medical Media : Distributed by Oxford University Press, 1997)
Cognitive Decline - Strategies for Prevention examines the problems associated with our understanding of the aging brain, whether or not such decline is inevitable and if there are practical steps which can be taken to prevent or minimise cognitive decline in late life. Our knowledge about the prevention of cognitive decline and dementia in old age has grown rapidly in recent years and it is becoming clear that preventive strategies are now viable.
Based on a symposium sponsored by the International Longevity Center (ILC-US), the Mount Sinai Medical Center, New York.
Keywords: Cognition in old age.; Cognition disorders in old age -- Prevention.; Cognition.; Older people.; Cognition; Cognition Disorders -- prevention & control; Aging -- physiology; Aged; Cognition chez la personne âgée.; Personnes âgées.; cognition.; elderly.; MEDICAL -- Geriatrics.; MEDICAL -- Nursing -- Gerontology.; Older people; Cognition disorders in old age -- Prevention; Cognition in old age